Levosimendan Reduces Prostaglandin F2a-dependent Vasoconstriction in Physiological Vessels and After Experimentally Induced Subarachnoid Hemorrhage - Wanderer, Stefan; Mrosek, Jan; Gessler, Florian; Seifert, Volker; Konczalla, Juergen (Current Neurovascular Research, 2018)
Background: Delayed cerebral vasospasm (dCVS) following aneurysmal subarachnoid hemorrhage (aSAH) is (next to possible aneurysm rebleeding, cortical spreading depression and early brain injury) one of the main factors contributing to poor overall patient outcome. Since decades, intensive research has been ongoing with the goal of improving our understanding of the pathophysiological principles underlying dCVS. Endothelin-1 (ET-1) and prostaglandin F2 alpha (PGF2a) seem to play a major role during dCVS. The synthesis of ET-1 is enhanced after subarachnoid hemorrhage (SAH) to mediate a long-lasting vasoconstriction, and PGF2a contributes to cerebral inflammation and vasoconstriction. Under physiological conditions, levosimendan (LS) demonstrates an antagonistic effect on PGF2a-induced cerebral vasoconstriction. Thus, the intention of the present study was to analyze potentially beneficial interactions in a pathophysiological situation. Methods: A modified double hemorrhage model was used. Functional interactions between the calcium-sensitizing action of LS and the vasoconstrictive properties of PGF2a were investigated. Results: After pre-incubation with LS, followed by application of PGF2a, a significant decrease in maximum contraction (Emax) for sham-operated animals was found (Emax 28% with LS, Emax 56% without LS). Using the same setting after SAH, the vessel segments did not reach a statistically significant contraction (but similar like the sham-operated vessels), neither for Emax nor pD2 (-log10EC50) nor EC50 (i.e., the concentration at which half of the maximal effect occurs). LS series in sham animals were performed by pre-incubation with PGF2a. The resultant Emax showed a statistically strong significance concerning a higher vasorelaxation compared with a solvent control group. Vessel segment relaxation was significantly stronger in the same experimental setup after SAH. Conclusion: Under physiological and pathophysiological circumstances, LS reduced and dosedependently reversed PGF2a-induced vasoconstriction. These results can be applied to further developing methods to antagonize dCVS after aSAH.
Keywords: aneurysmal Subarachnoid Hemorrhage (aSAH)